Pharmacological Properties of Vochysia Haenkeana (Vochysiaceae) Extract to Neutralize the Neuromuscular Blockade Induced by Bothropstoxin-I (Lys49 Phospholipase A2) Myotoxin - Carolina Harder; Akila Lara de Oliveira; Andreia Borges Scriboni; Adélia Cristina Oliveira Cintra; Raphael Schezaro-Ramos; Márcio Galdino dos Santos; Karina Cogo-Müller; Regina Yuri Hashimoto Miura; Rafael Stuani Floriano; Sandro Rostelato-Ferreira; Yoko Oshima-Franco (Tabriz University of Medical Sciences, 2017)
Purpose: Bothrops snakes are responsible for more than 70 % of snakebites every year in Brazil and their venoms cause severe local and systemic damages. The pharmacological properties of medicinal plants have been widely investigated in order to discover new alternative treatments for different classes of diseases including neglected tropical diseases as envenomation by snakebites. In this work, we have investigated the ability of Vochysia haenkeana stem barks extract (VhE) to neutralize the neuromuscular effects caused by Bothropstoxin-I (BthTX-I), the major phospholipase A2 (PLA2) myotoxin from B. jararacussu venom. Methods: The biological compounds of VhE were analysed under thin layer chromatography (TLC) and its neutralizing ability against BthTX-I was assessed through twitch-tension recordings and histological analysis in mouse phrenic nerve-diaphragm (PND) preparations. The antimicrobial activity of VhE was assessed against S. aureus, E. coli and P. aeruginosa strains. The aggregation activity of VhE was analysed under protein precipitation assay. Results: VhE showed the presence of phenolic compound visualized by blue trace under TLC. VhE abolished the neuromuscular blockade caused by BthTX-I applying the pre-toxin incubation treatment and partially neutralized the BthTX-I action under post-toxin incubation treatment; VhE contributed slightly to decrease the myotoxicity induced by BthTX-I. The neutralizing mechanism of VhE may be related to protein aggregation. VhE showed no antimicrobial activity. Conclusion: V. haenkeana extract which has no antimicrobial activity exhibited neutralizing ability against the neuromuscular blockade caused by BthTX-I and also contributed to decrease its myotoxicity. Protein aggregation involving phenolic compounds may be related in these protective effects.